Strategi Kebudayaan Kesenian Jaranan di tengah Modernisasi: Potret Jaranan Okta Putri Kencono Kota Surabaya - Oktavia, Nur Laili; Sudrajat, Arief (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2024)
Jaranan as the traditional heritage of the people of East Java, Surabaya faces great challenges due to urbanization and globalization. The Jaranan Okta Putri Kencono group, although new, managed to survive in the midst of social changes and competition with other art groups. This study examines the cultural strategies applied by this group to adapt to modernization. This research reveals how technological and social adaptations are applied in maintaining the existence of traditional arts amid declining interest in modern entertainment. This qualitative research examines Okta Putri Kencono cultural strategy in adapting to modernization in Surabaya. The study was conducted in Lakarsantri and Wiyung, Surabaya which were chosen because of their relevance to the group's origins and appearance. We triangulated between observation, interview, and documentation as our data collection methods. Interview was conducted with various members of the Okta Putri Kencono group, consisting of consists of the founder, leader, and bopo; bopo senior; and sound system administrator.The study show that three phases faced by Jaranan Okta Putri Kencono group are mythical phase, ontological phase, and functionalist phase. In the mystical phase, Jaranan still maintains spiritual rituals such as offerings as a tribute to ancestors. The ontological phase is characterized by the reinterpretation of traditional values to answer the challenges of modern society, including adaptation to performance elements without leaving traditional identities. Meanwhile, the functionalist phase adapts to modernization, Okta Putri Kencono integrates modern elements, such as audiovisual technology, updated story themes, and collaborations with young artists and creative communities. In essence, the Jaranan Okta Putri Kencono group has successfully navigated the challenges of modernity while preserving its rich cultural heritage. By adapting to changing times, the group ensures the continued vitality of the Jaranan tradition for future generations.